Controlled-source electromagnetic data from the TAG hydrothermal field, 26N Mid-Atlantic Ridge - Gehrmann, Romina A S (Supplement to: Gehrmann, Romina A S; North, Laurence J; Graber, Sebastian; Szitkar, Florent; Petersen, S; Minshull, Tim A; Murton, Bramley J (2019): Marine Mineral Exploration With Controlled Source Electromagnetics at the TAG Hydrothermal Field, 26°N Mid-Atlantic Ridge. Geophysical Research Letters, 46(11), 5808-5816, https://doi.org/10.1029/2019GL082928, 2019)
Raw data from electromagnetic survey at the Mid-Atlantic Ridge 26N (JC138, cruise report https://www.bodc.ac.uk/resources/inventories/cruise_inventory/report/16052/ ) , July 2016. Vulcan voltage logger binary files (Constable, S. et al. 2016, Scripps Institution of Oceanography) and DASI electric current transmitter .tdms files (Sinha et al. 1990, University of Southampton) can be read with the Matlab scripts attached (scripts to read Vulcan data are also found at http://marineemlab.ucsd.edu/Projects/lcplot/). Navigation files include CTD measurements at DASI, pressure at each instrument, USBL data for DASI and the end of the array, winch/deep tow cable data, and internal compass readings for the towed Vulcan receivers, some of which are .mat files that can be read with Matlab.
Keywords: Blue Mining; CSEM; Massive Sulphides; Mid-Atlantic Ridge; TAG